English Interference in Indonesian Language in @folkshitt Instagram Caption: A Sociolinguistic Case Study - Lisdayani, Fika; Suprayogi, Suprayogi (Faculty of Arts and Education, 2025)
In Indonesia, the internet has become crucial for communication, with 221.5 million users as of May 2024. This study investigates the influence of English on Bahasa Indonesia in Instagram captions by @folkshitt, focusing on phonological and orthographic adaptations. The objective is to understand how these changes shape digital communication and reflect cultural nuances. Using qualitative analysis, the researcher examined posts from June 1st to 20th, 2024, identifying instances of English interference in Indonesian sentences. The analysis covered phonological, morphological, syntactic, and lexical aspects, employing sociolinguistic and Computer-Mediated Communication (CMC) theories. The findings reveal significant lexical borrowing, phonological interference in code-switching, and orthographic changes in English words adapted to Indonesian. These examples highlight the dyknamic interaction between the two languages and the creative ways bilingual speakers navigate them. Empirically, this research provides concrete examples of English’s influence on Bahasa Indonesia in social media. Conceptually, it offers insights into language contact and the impact of digital environments on linguistic landscapes, emphasizing the role of digital platforms in shaping language norms and cultural representation.